(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background External anogenital warts are considered the commonest viral sexually transmitted infection that has serious negative psychological effects. Various destructive modalities have been tried with variable results with high recurrence rates in contrast to intralesional immunotherapy. Aim to evaluate the efficacy, safety, and tolerability of intralesional Measles Mumps Rubella (MMR) vaccine versus intralesional and intradermal purified protein derivative (PPD) in treatment of female anogenital wart. Methods This randomized clinical trial included 69 female patients with anogenital warts above 18 years old divided into three equal groups. Group 1 received intralesional MMR at a dose of (0.2 ml) in the largest wart, group 2 received intralesional (IL)PPD (0.2 ml) in the largest wart, group 3 received intradermal(ID) PPD (0.2 ml) every 2 weeks till improvement or for a maximum five treatment sessions. The follow up period was 6 months after the last treatment session. Results Although it was not statistically significant, overall response was higher in the MMR group (78.3 %) versus IL PPD ( 69.6%) and ID PPD (56.5%).. The highest cure rates were after the 4th session in the MMR group and the 5th session in both IL PPD and ID PPD groups with slightly lower numbers of sessions needed for cure in the MMR group (4 sessions) versus both PPD group (5 sessions). IL PPD group showed non statistically significant higher rates of complications in comparison with ID PPD and MMR group. IL PPD showed higher rates of recurrence than MMR and ID PPD groups during the follow up period without significant difference. There was significant difference between level of IL12 before and after treatment in every group. In addition, there was significant difference between level of IL12 after treatment between IL PPD and other both groups. Conclusion MMR , intralesional PPD and intradermal PPD are effective in female anogenital warts with higher safety profile of MMR.